2011
DOI: 10.1111/j.1442-2042.2011.02933.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide transcriptome analysis of fluoroquinolone resistance in clinical isolates of Escherichia coli

Abstract: Abbreviations & AcronymsObjectives: Coincident with their worldwide use, resistance to fluoroquinolones in Escherichia coli has increased. To identify the gene expression profiles underlying fluoroquinolone resistance, we carried out genome-wide transcriptome analysis of fluoroquinolone-sensitive E. coli. Methods: Four fluoroquinolone-sensitive E. coli and five fluoroquinolone-resistant E. coli clinical isolates were subjected to complementary deoxyribonucleic acid microarray analysis. Some upregulated genes' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Due to the technological advances in next generation sequencing, profiling of a large panel of different cells under various environmental conditions has become possible and led to the acquisition of extensive RNA-sequencing datasets (Wang et al, 2009;Yamane et al, 2012;Dötsch et al, 2015;Khaledi et al, 2016). Those have been used to shed light on environment-driven flexible changes in the transcriptional profile.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the technological advances in next generation sequencing, profiling of a large panel of different cells under various environmental conditions has become possible and led to the acquisition of extensive RNA-sequencing datasets (Wang et al, 2009;Yamane et al, 2012;Dötsch et al, 2015;Khaledi et al, 2016). Those have been used to shed light on environment-driven flexible changes in the transcriptional profile.…”
Section: Introductionmentioning
confidence: 99%
“…Прежде всего для многих бактерий альтернативой устойчивости является способ-ность адаптации к фторхинолонам, связанная с замедлением метаболизма, репликации ДНК и деления клеток, а также формированием биопленок [13,21,70,84].…”
Section: роль дополнительных механизмов в развитии устойчивости к фтоunclassified
“…Поскольку действие фторхинолонов на-правлено на ДНК, активация систем репара-ции важна для сохранения жизнеспособности [13,21,84]. Это было показано при исследо-вании влияния мутаций по гену ncr, продукт которого является репрессором системы репа-рации RecCBD, на устойчивость Acinetobacter baumannii к ципрофлоксацину.…”
Section: роль дополнительных механизмов в развитии устойчивости к фтоunclassified
“…There are many environments or human tissues during therapy where bacteria are exposed to low concentrations of antibiotic (less than minimum inhibitory concentration, MIC). Many studies have shown the profound transcriptomic changes in the bacterial cells and their potential contributions to the evolution of resistance when exposed to low levels of cipro oxacin [2,3]. In the therapeutic use of cipro oxacin, levels of cipro oxacin in tissues or serum can be reach or exceed the MIC.…”
Section: Introductionmentioning
confidence: 99%